12.2k views
5 votes
Integrate each of the following 12 - lnx​

User Tashna
by
4.8k points

1 Answer

6 votes

Answer:


\displaystyle \int {(12 - lnx)} \, dx = x[13 - ln(x)] + C

General Formulas and Concepts:

Algebra I

  • Terms/Coefficients
  • Factoring

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Integration

  • Integrals
  • Indefinite Integrals
  • Integration Constant C

Integration Rule [Reverse Power Rule]:
\displaystyle \int {x^n} \, dx = (x^(n + 1))/(n + 1) + C

Integration Property [Multiplied Constant]:
\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx

Integration Property [Addition/Subtraction]:
\displaystyle \int {[f(x) \pm g(x)]} \, dx = \int {f(x)} \, dx \pm \int {g(x)} \, dx

U-Substitution

  • U-Solve

Integration by Parts:
\displaystyle \int {u} \, dv = uv - \int {v} \, du

  • [IBP] LIPET: Logs, inverses, Polynomials, Exponentials, Trig

Explanation:

Step 1: Define

Identify


\displaystyle \int {(12 - lnx)} \, dx

Step 2: Integrate Pt. 1

  1. [Integral] Rewrite [Integration Property - Addition/Subtraction]:
    \displaystyle \int {(12 - lnx)} \, dx = \int {12} \, dx - \int {lnx} \, dx
  2. [1st Integral] Rewrite [Integration Property - Multiplied Constant]:
    \displaystyle \int {(12 - lnx)} \, dx = 12\int {} \, dx - \int {lnx} \, dx
  3. [1st Integral] Reverse Power Rule:
    \displaystyle \int {(12 - lnx)} \, dx = 12x - \int {lnx} \, dx

Step 3: Integrate Pt. 2

Identify variables for integration by parts using LIPET.

  1. Set u:
    \displaystyle u = lnx
  2. [u] Differentiate [Logarithmic Differentiation]:
    \displaystyle du = (1)/(x) \ dx
  3. Set dv:
    \displaystyle dv = dx
  4. [dv] Integration Rule [Reverse Power Rule]:
    \displaystyle v = x

Step 4: Integrate Pt. 3

  1. [Integral] Integration by Parts:
    \displaystyle \int {(12 - lnx)} \, dx = 12x - \bigg[ xlnx - \int { \bigg( x \cdot (1)/(x) \bigg) } \, dx \bigg]
  2. [Integrand] Simplify:
    \displaystyle \int {(12 - lnx)} \, dx = 12x - \bigg[ xlnx - \int {} \, dx \bigg]
  3. [Integral] Reverse Power Rule:
    \displaystyle \int {(12 - lnx)} \, dx = 12x - \bigg[ xlnx - x + C \bigg]
  4. Simplify:
    \displaystyle \int {(12 - lnx)} \, dx = 12x - xlnx + x + C
  5. Factor:
    \displaystyle \int {(12 - lnx)} \, dx = x[12 - ln(x) + 1] + C
  6. Simplify:
    \displaystyle \int {(12 - lnx)} \, dx = x[13 - ln(x)] + C

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Integration

Book: College Calculus 10e

User Shobhit Sharma
by
5.6k points